Place-based practices in Sarawak literature in Chinese - Bong, Joo Ping (2013)
Sarawak Literature in Chinese is well known for its unique cultural landscape, its conscious attention to issues of writing, and the place-based practices of its major authors. These include the earlier generation of Wu An, Tian Si and Liang Fang, all famous for their depictions of nature and indigenous culture as well as the more contemporary rainforest imagination of authors like Zhang Guixing and the Borneo Memoirs of Li Yongping. This research attempts to situate the place-based practices of Sarawak Literature in Chinese within debates on issues of the "local" and "global" issues. At the same time, it attempts to explore the predominant image(s) and motifs of Sarawak Literature in Chinese. This research focuses on two main issues. Firstly, how the content of place-based practice is shown in Sarawak Literature in Chinese. Secondly, how such place-based practice responds to the dominant trends of globalization. Placebased practice for Sarawak Literature in Chinese is demonstrated through twelve facets. The imagination of the rainforest, details of hunting experiences, pastoral life,Sarawak’s landscape and exotic rainforest delicacies have made Sarawak Literature in Chinese unique. Local chronicles, biographies of major local figures, reflections on local history, thoughts on native customs and cultural interracial relations reveal Sarawak Literature in Chinese as a place-based practice. Furthermore, environmental issues and nature writing also closely related and respond to the threat and crises of globalization. The heterogeneity of place-based practices in Sarawak Literature in Chinese, regardless of the genre or the nature of the text, has a garnered much critical attention beyond regional borders.